2021
DOI: 10.1172/jci.insight.142945
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic acetylcholine receptor mediates right ventricular fibrosis and diastolic dysfunction in pulmonary hypertension

Abstract: Right ventricular (RV) fibrosis is a key feature of maladaptive RV hypertrophy and dysfunction and is associated with poor outcomes in pulmonary hypertension (PH). However, mechanisms and therapeutic strategies to mitigate RV fibrosis remain unrealized. Previously, we identified that cardiac fibroblast α7 nicotinic acetylcholine receptor (α7 nAChR) drives smoking induced RV fibrosis. Here we sought to define the role of α7 nAChR in RV dysfunction and fibrosis in the settings of RV pressure overload as seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 70 publications
(101 reference statements)
1
23
0
Order By: Relevance
“…α7nAChR has made a lot of progress in the research related to the improvement of cognitive function, and therapeutic effects of α7nAChR agonists on AD have been widely reported [ 41 ]. However, it has been reported that the activation of α7nAChR can promote the formation of fibrosis, atherosclerosis and right ventricular dysfunction [ 42 , 43 ]. Hence one can see that α7nAChR plays various, even contrary, functions on different types of cells and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…α7nAChR has made a lot of progress in the research related to the improvement of cognitive function, and therapeutic effects of α7nAChR agonists on AD have been widely reported [ 41 ]. However, it has been reported that the activation of α7nAChR can promote the formation of fibrosis, atherosclerosis and right ventricular dysfunction [ 42 , 43 ]. Hence one can see that α7nAChR plays various, even contrary, functions on different types of cells and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MCT-induced PH belongs to PAH (Group 1); in PAH patients, improvement in RV function was critical to lowering mortality ( Potus et al, 2015 ; Clapham et al, 2020 ). PAH induces an increase in RV afterload, which eventually results in fibrosis of RV myocardial tissue and RV dysfunction when the afterload exceeds RV compensatory capacity ( Vang et al, 2021 ). In our study, rats in the UK-cRGD-LIP group had considerably improved RV systolic function and RV pumping efficiency ( Figures 9B,E–G ) post targeted thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine-induced pulmonary hypertension, RV remodeling, and vascular dysfunction are ameliorated by α7 nicotinic cholinergic receptor knockout, and are absent in female mice ( 58 ). The pathogenesis of pulmonary hypertension induced by Sugen and hypoxia also involves α7 nicotinic cholinergic receptor-mediated cross-talk between cardiomyocytes and cardiac fibroblasts, leading to RV fibrosis ( 60 ). Treatment of cardiac fibroblasts isolated from the RV, but not the LV, with cigarette smoke extracts or 600 nM of nicotine stimulated fibroblast proliferation ( 61 ).…”
Section: Methodsmentioning
confidence: 99%